Fe2(CO)9-mediated [5+1] cycloaddition of vinylcyclopropanes and CO for the synthesis of α, β-cyclohexenones. Issue 22 (2nd June 2016) - Liu, Cheng-Hang; Zhuang, Zhe; Bose, Sritama; Yu, Zhi-Xiang
Abstract: A Fe2 (CO)9 -mediated [5+1] cycloaddition of vinylcyclopropanes (VCPs) and CO to α, β-cyclohexenones has been developed. The reaction can tolerate aryl and aliphatic groups at the α-position of VCPs, while VCP substrates with vinyl or alkynyl substitutions are not suitable ones. In addition, this reaction can also be used to synthesize bicyclic rings if an aryl group is attached to the vinyl moiety of the substrate. Compared to the Fe(CO)5 -mediated [5+1] reaction, the use of cheap and safe Fe2 (CO)9 and abandoning the photo-irradiation conditions are the two major advantages of the present method. Graphical abstract: